Charge Compensation Mechanism and Multifunctional Properties of Bi1−xBaxFeO3 (x = 0, 0.05, 0.1) Ceramics. (1st October 2022) - Sasmal, Abhishek; Sen, Shrabanee
Abstract : The charge compensation mechanism of Ba 2+ ion doped BiFeO3 (BFO) has been studied here in detail. The most common problem of high leakage current of ceramic BFO was noticeably resolved by significant reduction of charge defects through Ba 2+ doping. The leakage current density of Bi1-x Bax FeO3 (x = 0, 0.05, 0.1) was found to be reduced to ∼3.13 × 10 −8 A cm −2 for x = 0.1 from a value of 2.26 × 10 −4 A cm −2 for x = 0 at an applied field of 500 V cm −1 . This reduction of leakage current was caused by the reduction of charge defects which was verified through the X-ray photoelectron spectroscopy (XPS). The dielectric and ferroelectric properties of undoped and Ba 2+ doped BFO were also studied here explicitly and correlated with charge compensation mechanism. The structural and vibrational characterization proved the phase pure formation and the presence of metal-oxide bonds. The optical characterization showed the reduction in energy band gap with increased Ba 2+ doping in BFO (2.18, 1.71 and 1.56 eV for x = 0, 0.05 and 0.1, respectively). Another common problem of BFO, namely low remanent magnetization, was also significantly resolved through Ba 2+ doping in it and the strong antiferromagnetic BFO started showing weak ferromagnetic nature with increased doping concentration.